Pendopo lamp: educational diy lamp kit - Karim, Milhan; Abdullah Firdaus, Syauqi; Salsabila, Yasmin Qonita (2025)
Globalisation has changed the way society sees everything, including the convenience of educating others. For parents, they tend to choose the Pendopo way to educate their children about lessons at school or basic knowledge, which leads to a massive use of screen time by underage children. On the other hand, the fast growth of technology could damage the quality of mankind by degrading the children of future generations. The tools they use for learning are not as effective as the traditional way. It turns out that digital education could not reach the full potential of the best learning experience for children. Pendopo Lamp has a vision that is also a solution for the issue, which is to accompany the children in unleashing their curiosity to discover and create. The product will help in growing their abilities and educating them about various topics. This extended abstract describes how Pendopo Lamp was designed by analysing the issue and translating insights into a meaningful product outcome.